Research on Customer satisfaction on the quality of E-Banking services in Vietnamese Commercial Banks - Pham, The Tuyen (2020)
Research on service quality and service quality satisfaction has attracted a great deal of attention from scholars over the past two decades and has provided many valuable findings to society. This study was conducted to measure and determine the factors affecting the quality of E-banking services based on SERVPERF model of Cronin and Taylor (1992) and the impact of E-banking services to customers' satisfaction when using E-banking services at 5 commercial banks in Vietnam: VCB, BIDV, ACB, Techcombank, Vietinbank. Data were collected by interviewing 337 individual customers who have been using E-banking services at these five commercial banks for 1-3 years. Methods such as descriptive statistics, Cronbach's Alpha coefficients, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and the Structural Equation Model (SEM) were used in this study. The results show that the quality of E-banking services is influenced by the six factors in the order of importance: Reliability, Responsiveness, Empathy, Assurance, Tangibles, Accessibility. In addition, the quality of E-banking services has also positively impacted the satisfaction of customers in these five commercial banks.